A relação umidade/proteína no camarão branco do pacífico litopenaeus vannamei como um parâmetro de identificação de fraude por adição de água - Oliveira, Maria Érica da Silva (Universidade Federal Rural do Semi-Árido, 2019)
Considering the temperature fluctuation during the seafood cold chain, where the product are submitted to the freeze-thaw cycles, the common practices importation, exportation and market, the objective of the present study was to evaluate the efficacy of several humectant food additives in L. vannamei after two freeze-thaw cycles, and at the same time whether the moisture-protein ratio of fresh and frozen-thawed shrimp (treated or not with additives) may be useful in the economic fraud identification by water addition. Fresh shrimp samples were submitted to the following 8 treatments: Control (C – fresh shrimp); T1 (distilled water); T2 (5% NaCl); T3 (5% sodium tripolyphosphate STPP); T4 (5% CARNAL 961); T5 (5% NP-30); T6 (5% BRIFISOL 450); and T7 (5% BRIFISOL S5). All solutions were made with cold distilled water (5ᵒC) and the immersion time was settled in 60 min. The samples were divided into two groups: GROUP I – samples that were immersed and submitted to the 1st freezing (-35ºC/24 h), storage (-35ºC/15 days), 1st thawing (5ºC/24 h), 2nd freezing (-35ºC/24 h), storage (-35ºC/15 days), and 2nd thawing (5ºC/24 h) and GROUP II – samples that were immersed again with the same additives after 1st thawing (5ºC/24 h) and follow the 2nd freezing, storage and thawing. After each step, the yield (%) was determined and the physical-chemical analyzes were carried out (moisture, protein, sodium, phosphate, pH and water holding capacity - WHC). Additives were efficient in weight gain and weight loss reduction of the samples. For the values of moisture, protein and moisture-protein ratio (MPR), it was verified that there was a significant difference (p <0.05) between samples immersed in humectant additives and control. The effectiveness of the additives in WHC depended on the number of thawing cycles. The highest pH value found was 8.62 (sample treated with NP-30), exceeding the limits established by the legislation for shrimp (7,85). The highest phosphate levels were found in samples treated with STPP, CARNAL-961, BRIFISOL 450 and BRIFISOL S5. For all samples treated with additives, there was an increase in sodium content. Principal component analysis (PCA) showed that the two immersions and the different additives used were determinant for the behavior of the variables. The results indicated that the use of humectant food additives at the concentration and time suggested in this study was not able to exceed the MPR limits established by Brazilian legislation, proving that this parameter should be re-evaluated
Keywords: pescado; camarão; qualidade; retenção de água; aditivos; fraude; seafood; shrimp; quality; water retention; additives; fraud; CIENCIAS AGRARIAS::MEDICINA VETERINARIA